Early maternal complications of cesarean section in two technique of Closure and non-closure of parietal peritoneum: a double blind randomized clinical trial - Mehrnush Mostafaei; Behzad Imani; Shirdel Zandi; Soghra Rabiei (Mashhad University of Medical Sciences, 2021)
Introduction: Cesarean section is performed with two technique of closure or non-closure of the peritoneum, but there is disagreement about the advantages and disadvantages of these techniques. Accordingly, this study was performed with aim to compare the early maternal complications of cesarean section in two technique of closure or non-closure of the parietal peritoneum. Methods: This double-blind randomized clinical trial study was performed on 120 patients undergoing cesarean section at Hamadan Fatimah Hospital in 2019. Samples were randomly divided into two groups: closure of the peritoneum (n=60) and non-closure of the peritoneum (n=60). The maternal complications during and after surgery were recorded. Data were analyzed by SPSS software (version 21) and Chi-square, independent t-test and repeated measures. Results: The results showed that operative time and bleeding during surgery were significantly fewer in patients receiving non-closure technique (p<0.05). Also, the duration of ileus, the amount of received analgesic, and pain 12 and 24 hours after the surgery were significantly lower in patients receiving non-closure technique (p <0.05). However, there was no significant difference between the two groups in terms of pain after 6 hours of the surgery and the symptoms of surgical wound infection (p> 0.05). Conclusion: The complications such as bleeding during surgery, the duration of surgery, ileus after surgery, pain, and consumption of analgesic will occurs with less intensity in patients receiving non-closure technique than patients with closure technique; however, these two methods were not different in terms of surgical wound infection.